2016
DOI: 10.1016/j.cancergen.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Digitally guided microdissection aids somatic mutation detection in difficult to dissect tumors

Abstract: Molecular genetic testing on formalin fixed, paraffin embedded (FFPE) tumors frequently requires dissection of tumor from tissue sections mounted on glass slides. In a process referred to as “manual macrodissection,” the pathologist reviews an H&E stained slide at the light microscope and marks areas for dissection, and then the laboratory performs manual dissection from adjacent sections without the aid of a microscope, using the marked reference H&E slide as a guide. Manual macrodissection may be inadequate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…The dissected material contained a variety of cell types such as lymphocytes, fibroblasts, acinar cells, besides the target IPMN epithelium. Additionally, the proportion of neoplastic content is different and low in samples 60 , even though their sample sizes are same. However, the study did not compare subtle difference of genetic or epigenetic aberrations between malignant-potential dissected regions, and just compare between malignant-potential and benign dissected regions.…”
Section: Discussionmentioning
confidence: 97%
“…The dissected material contained a variety of cell types such as lymphocytes, fibroblasts, acinar cells, besides the target IPMN epithelium. Additionally, the proportion of neoplastic content is different and low in samples 60 , even though their sample sizes are same. However, the study did not compare subtle difference of genetic or epigenetic aberrations between malignant-potential dissected regions, and just compare between malignant-potential and benign dissected regions.…”
Section: Discussionmentioning
confidence: 97%
“… 25 For example, Geiersbach et al found that the estimated neoplastic cellularity and KRAS mutant allele fraction were significantly higher in samples obtained by mesodissection, and 7 of the 32 samples (22%) showed a detectable mutation only with this technology. 21 Gustafson et al found that the automated dissection of tumor AOIs could detect variants that would otherwise go undetected in 70% of cases, some of which, importantly, were clinically actionable mutations. 25 To date, other complex molecular tests, such as expression analysis, have not been assessed using this system.…”
Section: Discussionmentioning
confidence: 99%
“…Given its high cost and complexity, laser‐guided microdissection is also not recommended to be used, apart from very rare cases where small areas or individual cells are essential to be analysed. With the current rapid development in digital pathology applications, other digitally guided dissection systems could enter laboratory practice during the next decade …”
Section: Discussionmentioning
confidence: 99%